A Vicious Cycle: Probable Psychological Distress and Maladaptive Cognition as Barriers to Remediation Among Indonesian Medical Students Failing National Licensure - Gladys Putri; Mary-Jane Wood; Zahra Amir; Novalika Kurnia (HM Publisher, 2025)
Introduction: Failure on high-stakes medical licensing examinations, such as the Indonesian Medical Doctor Competency Examination (UKMPPD), is a significant stressor. This study aims to delineate the current psychological profile of